Environment and Offspring Surveillance in Porcine Brucellosis - Rebollada-Merino, Agustín; Pérez-Sancho, Marta; Rodríguez-Bertos, Antonio; García, Nerea; Martínez, Irene; Navarro, Alejandro; Domínguez, Lucas; García-Seco, Teresa (Frontiers in Veterinary Science, 2022)
Porcine brucellosis (Brucella suis) is a notifiable disease causing significant economic losses in production systems. Most infected pigs may act as carriers and shedders even if asymptomatic, contributing to B. suis environmental persistence and hindering control efforts. Here, we present the results of an indirect surveillance programme during and after a B. suis outbreak focused on the offspring and the environment in the context of a two-year-old control programme at a sow breeding farm. Post-weaning pigs were monitored using indirect enzyme-linked immunosorbent assay (I-ELISA) and a brucellin skin test (BST) to evaluate how they reacted in the context of a B. suis outbreak. The novel environmental surveillance programme was successfully implemented using gauze sponges pre-hydrated in a surfactant and a B. suis-inactivating liquid for pathogen nucleic acid detection. This approach has proven to be a simple, practical, valuable and safe method for animals to detect and monitor B. suis. Environmental sampling and offspring surveillance may provide complementary information on B. suis epidemiology and may complement surveillance programmes in order to improve B. suis control.